Whose Story Am I?: Redescribing Profound Intellectual Disability in the Kingdom of God - Swinton, John (Journal of religion, disability & health, 2011)
This article reflects theologically on the spiritual lives of people with profound intellectual disabilities. It offers a fresh way of exploring the theological contribution that such life experiences have for an understanding of God, human being, and what it means to be a church. By meditating on the storied nature of human beings, this discussion offers a narrative mode of resistance that seeks to develop powerful counternarratives that stand as a challenge to the “normal” stories told about people with profound intellectual disabilities. The discussion examines key questions around what it means to know God even when, intellectually, one might not know anything about God.